115k views
1 vote
For f(x)=4x+1 and g(x)=x^2-5, find (f+g)(x)

User Dgtized
by
4.8k points

1 Answer

5 votes

For this case we have the following functions:


f (x) = 4x + 1\\g (x) = x ^ 2-5

We must find
(f + g) (x). By definition we have to:


(f + g) (x) = f (x) + g (x)

So:


(f + g) (x) = (4x + 1) + (x ^ 2-5) = 4x + 1 + x ^ 2-5 =

Different signs are subtracted and the major sign is placed.


(f + g) (x) = x ^ 2 + 4x-4

Answer:


(f + g) (x) = x ^ 2 + 4x-4

User Ossentoo
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.